INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2009-2017: indonesia - Agusta, Christina; Radianto, Wirawan E.D. (Media Akuntansi dan Perpajakan Indonesia, 2020)
This purpose of this research is to analyze the impact of intellectual capital on the companies performance. The research used quantitative approach, and it collected by annual reports to pharmaceutical company at Indonesia Stock Exchange (IDX) from year 2009–2017 which had a population of 10 companies. The hypothesis of this research is tested by using multiple regression analysis. The result indicate that (1) intellectual capital has positive influence to the companies performance (ROA and ROE); (2) intellectual capital has negative influence on companies performance (ATO and MBV). Hence, to maximize the performance on pharmaceutical companies merely consider intellectual capital factors.